RANCANG BANGUN PENGUKURAN SUHU DAN KELEMBABAN PADA PENYIRAMAN OTOMATIS UNTUK TANAMAN KACANG TANAH BERBASIS IOT - Nugroho, Nicholas Herdiyanto; K N, Nurwijayanti (Universitas Dirgantara Marsekal Suryadarma, 2025)
Efficient, automated watering is crucial in modern agriculture. IoT (Internet of Things)-based automatic watering offers a solution to this challenge, particularly for peanut plants, which require precise and accurate watering. This research aims to design and test an IoT-based automatic watering system for peanut plants. The system is designed to optimize water use and increase efficiency in peanut cultivation. Identified problems include difficulty in determining the correct amount of water, water wastage due to manual watering, and inaccurate visual observations. This research focused on the design of the automatic water regulation system, the water pump control method, and the sensitivity of the soil moisture sensor in the system. Test results showed that the system performed well. The soil moisture sensor can detect water levels and automatically control the water pump. The water pump activates when soil moisture is below 30% and shuts off when it reaches 60%. There was no discrepancy between the sensor readings and manual calculations, demonstrating the system's accuracy.